The Language Environment and its Role in Language Acquisition for Students of Class 5 Darussalam Modern Gontor Islamic Institution for Girl - Ahmad Hidayatullah Zarkasyi; Muthmainnah Choliq; Siti Nur Khodijah Binti H. Abu Samah (At-Ta'dib, 2022)
Darussalam Modern Gontor Islamic Institution is one of the Islamic educational institutions that pay great attention to language development and places it in an essential position through the creation of a formal and natural language environment. Moreover, it is used as the official language for students in daily communication. Besides, this language was implemented for activities and movements with an Arabic environment. This study aims to determine the formation of the language environment and its role in language acquisition for students of class 5 Darussalam Modern Gontor Islamic Institution for girls Campus 1 Sambirejo Mantingan Ngawi, East Java, especially in speaking skills. description. This research shows that the quality of a good, interesting, and abundant language environment plays a pivotal and effective tool in language learning, for this reason, the practice of using Arabic in daily life communication in both formal and natural environments should be considered. So that students of class 5 Darussalam Modern Gontor Islamic Institution 1 for girls Campus Sambirejo Mantingan Ngawi, East Java, can gain the goal of learning the language, namely the acquisition of a second language, especially in speaking skills.